Fiber-wireless for smart grid: A survey - Radzi N.A.M.; Ridwan M.A.; Din N.M.; Abdullah F.; Mustafa I.S.; L-Mansoori M.H. (EDP Sciences, 2023)
Smart grid allows two-way communication between power utility companies and their customers while having the ability to sense along the transmission lines. However, the downside is such, when the smart devices are transmitting data simultaneously, it results in network congestion. Fiber wireless (FiWi) network is one of the best congestion solutions for smart grid up to date. In this paper, a survey of current literature on FiWi for smart grid will be reviewed and a testbed to test the protocols and algorithms for FiWi in smart grid will be proposed. The results of number of packets received and delay vs packet transmitted obtained via the testbed are compared with the results obtained via simulation and they show that they are in line with each other, validating the accuracy of the testbed. The Authors, published by EDP Sciences, 2017.